Analisis Kesulitan Membaca Pemahaman Unsur Intrinsik Teks Cerita pada Siswa Kelas III Sekolah Dasar - Ayu Sagita; Saeful Mizan; Wendri Wiratsiwi (Universitas Islam Nahdlatul Ulama Jepara, 2026)
Reading comprehension difficulties in elementary schools remain a fundamental issue, particularly regarding the intrinsic components of narrative texts. This study aimed to deeply analyze and map the types and levels of difficulties faced by third-grade students at UPT SDN Banjar in understanding intrinsic story elements, as well as to identify their underlying causes. Employing a qualitative descriptive approach with a case study design, data were gathered from seven purposively selected participants using an initial ability test, observations, interviews, and questionnaires. The data analysis strictly focused on an interactive qualitative model (data reduction, display, and conclusion drawing), utilizing quantitative scores and percentages solely as supporting data to reinforce the depth of the qualitative interpretation. The findings highlight that the primary form of reading comprehension difficulty experienced by students is cognitive paralysis at the inferential reading level, characterized by severe barriers in processing, connecting, and interpreting implicit information within the story, despite being highly fluent in mechanical oral reading. As a manifestation of this form of difficulty, the plot (sequencing chronological cause-and-effect events) and moral values (extracting hidden messages) became the most difficult intrinsic elements for students to comprehend. These difficulties were driven by internal factors, including a weak holistic understanding of story structures and limited concentration on long texts, alongside instructional factors, which included teacher-centered instruction, minimal classroom interaction, and a limited variety of learning media. Therefore, interactive and contextual learning innovations are required to boost students' reading comprehension literacy.